2018
DOI: 10.1515/jbcpp-2017-0189
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the immunomodulatory and antibacterial activity of Termitomyces letestui (Pat.) Heim (Lyophyllaceae), an edible mushroom from Cameroon

Abstract: Background Globally, Termitomyces letestui is used by different communities to treat various illnesses, including bacterial infection, although with limited scientific evidence. The current study aims to assess the immunomodulatory and antibacterial properties of the water extract of a wild mushroom, T. letestui in mice model. Methods The base study was completed following the standard methods and procedures using white mice Mus musculus. The immunomodulatory was investigated for humoral and cell-mediated resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…But, some reports have shown the immunostimulatory effect of mushroom. For example, our previous study on the aqueous extract T. letestui and T. clepeatus showed a good dose-response effect in antibody production and hypersensitivity test in vivo in mice [26,27]. Study carried out on various mushroom 'species such as Amauroderma rude, showed that mushrooms 'species can increase the immunological capacities of spleen lymphocytes, macrophages and natural killer cells as well as macrophage metabolism and antibody production [14].…”
Section: Discussionmentioning
confidence: 99%
“…But, some reports have shown the immunostimulatory effect of mushroom. For example, our previous study on the aqueous extract T. letestui and T. clepeatus showed a good dose-response effect in antibody production and hypersensitivity test in vivo in mice [26,27]. Study carried out on various mushroom 'species such as Amauroderma rude, showed that mushrooms 'species can increase the immunological capacities of spleen lymphocytes, macrophages and natural killer cells as well as macrophage metabolism and antibody production [14].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Termitomyces have shown significant results in reacting against various human pathogenic bacteria and some fungal pathogens, but no studies have yet been undertaken involving other microorganisms [ 133 ]. Among the various Termitomyces species, T. clypeatus , T. eurrhizus , T. heimii , and T. robustus showed significant antimicrobial activity against different pathogenic microorganisms [ 234 , 247 , 248 , 249 , 250 , 251 ]. Some polysaccharides (endo- and exo-polysaccharides) from T. heimii also showed significance antimicrobial activity against different micro-organisms [ 152 , 251 ].…”
Section: Research On Antimicrobial Activitymentioning
confidence: 99%